Indian land sales and allotment in Antebellum Virginia: trustees, tribal agency, and the Nottoway reservation. Issue 2 (3rd May 2016) - Woodard, Buck
ABSTRACT: Though they had been vital agents in the backwoods diplomacy of the eighteenth century, through colonial warfare and treaties, Virginia politically and militarily subjugated the Iroquoian-speaking Nottoway as "tributaries" of the English Crown. Two Nottoway "Indian Towns" were surveyed and the surrounding lands held "in trust." Eventually, the House of Burgesses appointed "Trustees" to assist with select tribal land sales and the management of monetary distributions. Situated in Southampton County, Virginia, the antebellum Nottoway community was politically active: they petitioned the legislature, governors, and county courts to intercede on matters related to the mismanagement of their funds, distribution of property, illegal seizure, and treaty obligations. In contrast, by the end of the century, the Nottoway were described by contemporaries as "very few left in the county, " all reservation lands had been allotted, and their trustees dismissed. This paper explores Indian–white interactions within Southampton's antebellum political economy. The financial relationship between the tribe and their trustees is analyzed, as are the catalysts for Nottoway land sales and reservation allotment. The role of matrilineal leadership figures in Nottoway Trustee discourse and a series of asymmetries that emerged as the result of the tribe's engagement with the capitalist system are considered. This essay also examines Southampton's competition for control of Indian land and monetary capital in order to explicate the underlying causes of socio-cultural transformation. The prime mover of this change was economic, as community members struggled with their trustees for control of Indian resources and became more fully engaged in the cash-crop economy of the region.